Pengaruh Penggunaan Media Tutup Botol Bersukukata dalam Meningkatkan Keterampilan Membaca Kelas 1 MI Darul Hidayah Desa Gambirono Kecamatan Bangsalsari Kabupaten Jember - Yanuardianto, Elga; Alfia, Alfia (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The low reading proficiency of children served as the driving force for this study. This poor performance is believed to be caused by a lack of stimulation suited to the stages of early childhood development, particularly in relation to the students' disinterest in the teaching materials. The purpose of this study is to ascertain how using syllable-rich bottle cap media can help first-grade students at MI Darul Hidayah in Bangsalsari District, Jember Regency, improve their reading abilities. Pre- and post-tests are used in this kind of research, including control and experimental groups. The 22 students that made up the population of all subjects were split into two groups (control and experiment). The method used to gather data on the reading abilities of first-graders at MI Darul Hidayah, Gambirono Village, Bangsalsari District, Jember Regency, was asking students written questions. The SPSS software, version 25, is used in the data collection method. The average pre-test reading skills of the experimental class differ from the post-test reading skills of the experimental class test, as shown by the sig (2-failed) value of 0.00 < 0.05, according to the findings of the hypothesis testing using the paired sample t test. Aside from that, the experimental class's average pre-test score was 62.37, which was lower than the class's average post-test score of 83.18. So it can be concluded that there is an influence of using syllabic bottle cap media in improving the reading skills of grade 1 students at MI Darul Hidayah, Gambirono Village, Bangsalsari District. Thus the hypothesis in this research is accepted.